2012
DOI: 10.1039/c2jm35545k
|View full text |Cite
|
Sign up to set email alerts
|

Strongly adhesive and flexible transparent silver nanowire conductive films fabricated with a high-intensity pulsed light technique

Abstract: Large-scale silver nanowire (AgNW) mesh films have received increasing attention as new transparent conductive films used in various printed devices. However, there are two crucial issues in implementing AgNWs that need to be addressed: (1) strong adhesion between AgNW film and substrate and (2) high conductivity with short treatment time for low-cost printed technology. Here, a high-intensity pulsed light (HIPL) sintering technique, which provides extreme heating locally in the AgNW film and at the interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
172
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(179 citation statements)
references
References 24 publications
5
172
0
Order By: Relevance
“…Moreover, the high temperature sintering required in these processes hinders the use of temperature-sensitive materials. Fortunately, a simpler and much faster technique called high-speed photonic sintering has paved the way to directly embed AgNWs in a matrix at room temperature [31][32][33]. Photonic sintering has been recently developed to replace conventional thermal sintering of metal nanoparticles, and works rapidly at room temperature on large scales through lightinduced heat generation in metallic nanostructures [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the high temperature sintering required in these processes hinders the use of temperature-sensitive materials. Fortunately, a simpler and much faster technique called high-speed photonic sintering has paved the way to directly embed AgNWs in a matrix at room temperature [31][32][33]. Photonic sintering has been recently developed to replace conventional thermal sintering of metal nanoparticles, and works rapidly at room temperature on large scales through lightinduced heat generation in metallic nanostructures [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, a simpler and much faster technique called high-speed photonic sintering has paved the way to directly embed AgNWs in a matrix at room temperature [31][32][33]. Photonic sintering has been recently developed to replace conventional thermal sintering of metal nanoparticles, and works rapidly at room temperature on large scales through lightinduced heat generation in metallic nanostructures [31][32][33][34][35][36][37]. Jiu et al also found that the residual heat generated by photonic sintering in the metal network could be used to achieve strong adhesion between the network and a flexible substrate due to the deformation of the polymer substrates [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AgNWs show poor adhesion to plastic films, 11 whereas CNTs show relatively strong adhesion. 16 Therefore, various techniques, including substrate surface modification, 12 encapsulation with a thin Teflon layer 13 and irradiation with highdensity pulsed light, 27 have been investigated. Despite these efforts, there is still a need for further progress in both coating processes and substrate materials to realize high transparent conductivity performance and strong adhesive properties simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…4, but they appear before any current flow and remain unchanged after welding so are, therefore, not from electromigration. Several others have reported the existence of surface particles on silver nanowires synthesized by the polyol method [29,30], but their origin is still unclear at this time and requires further study.…”
Section: Overlapped Junctionsmentioning
confidence: 99%